2021
DOI: 10.1177/00420980211045523
|View full text |Cite
|
Sign up to set email alerts
|

Critical urban theory in the Anthropocene

Abstract: Critical urban thinkers often imagine urbanisation and the Anthropocene as inevitably being companion processes. But is planetary urbanisation the necessary telos and spatial limit of life in the Anthropocene? Is urban resilience the final form of urban responses to climate change? Will (or should) the urban (as either spatial form or process) survive the upending impacts of climate change or adaptation? Or, if the Anthropocene is a time of deep environmental and epistemological upheaval without historical pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 79 publications
(112 reference statements)
0
10
0
Order By: Relevance
“…What was hidden comes to light : In her call to abandon the inherited frameworks of urban theory, Wakefield wonders: ‘Rather than a seemingly endless expanse of resilient cities and urban processes, might the Anthropocene’s environmental and human transformations produce something else?’ (Wakefield, 2022: 920). This paper has suggested that this is indeed the case, while insisting that is only by renouncing the paranoid projection of delusional signification typical of academic sense-making that such latent meanings and alternative realities can emerge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…What was hidden comes to light : In her call to abandon the inherited frameworks of urban theory, Wakefield wonders: ‘Rather than a seemingly endless expanse of resilient cities and urban processes, might the Anthropocene’s environmental and human transformations produce something else?’ (Wakefield, 2022: 920). This paper has suggested that this is indeed the case, while insisting that is only by renouncing the paranoid projection of delusional signification typical of academic sense-making that such latent meanings and alternative realities can emerge.…”
Section: Discussionmentioning
confidence: 99%
“…These circumstances have contributed to a proliferation of new urban theories (Rickards et al, 2016), inspired in part by the necessity to think the urban and the Anthropocene together as ‘an unthinkable threshold or limit condition – the hauntology of the Anthropocene and the hauntology of the urban, both implicated in a thinking of an ending: the end of the wild, the end of a world’ (Ruddick, 2015: 1118). But in a recent issue of Urban Studies , Stephanie Wakefield insists on ‘the need to push the call for abandoning inherited frameworks and pursuing relentless theoretical experimentation much further’, while learning to ‘open our eyes to mutations in urban form and process produced by contemporary capitalism’ (Wakefield, 2022: 920, 919).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, geographers, with their sensitivity to natural processes, land politics and socio-spatial inequality will generate new frameworks for urban theory. We can see, for example, how Nelson and Bigger (2022), Robin and Cástan Broto (2021), Wakefield (2021a, 2021b) and Long and Rice (2019), to name but a few, have built on urban political ecology to set out how material urban space might be framed in a new, climatically sensitized future scholarship. And there is deep terrain to be excavated: one that requires ‘earth scientists, social scientists, archaeologists, urban planners and civil engineers’ to work together on the city as landform (Dixon et al, 2018: p. 122) or marine biologists, consumption sociologists and urban governance theorists on how the water-based city might be freed from plastic waste (Hawkins, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing interest among theorists in the spectre of semi-inundated cities, a long-standing trope of science fiction and disaster genres (Dobraszczyk, 2017). Miami, particularly, has drawn the attention of Ariza (2022) and Wakefield (2021a). The latter describes different scenarios circulating around the ‘retirement of Miami’, a series of local discourses and activities which interpret how the city's existing urban fabric, prone to both mundane and extreme flooding events, is now seen as inadequate to withstand sea-level rise.…”
Section: New Climate New Urban Formsmentioning
confidence: 99%
“…Though the case of Greater Miami is in some ways unique, 2 it enables geographers to expand the field's conceptual and analytical limits and examine a wider range of experimental practices in knowing and governing the urban in the Anthropocene (Wakefield, 2021). In this paper, we thus situate GMB resilience initiatives within broader technopolitical struggles over how the urban can be rendered calculable in the Anthropocene.…”
Section: Introductionmentioning
confidence: 99%